EXPERIMENTAL ANALYSIS OF THE TRANSIENT BEHAVIOR OF AN ENGINE COOLING RADIATOR - Rodrigues, K.; Ieno, J. P. S.; Novazzi, L. F.; Albuquerque, C. (Revista de Engenharia Térmica, 2018)
The aim of this work is to study the behavior of an engine cooling radiator in a transient state, with circulation of heated water. An experimental apparatus was constructed with the radiator inside a wind tunnel. The water is pumped from a small water tank to a heater, passes through the heat exchanger, and returns to the tank. The tests were carried out with constant flowrates of water and air, and the heater was turned on and then off according to a pulse function. The temperatures of the radiator, the air and the water were measured on several points with thermocouples and a thermal camera. The flow of water and air were measured as well. A fast dynamics because of the radiator was observed, whereas a slow one was noticed due to water heating in the tank. The steady state was reached after 15 min. These results might be useful in the project of a vehicle cooling system under transient conditions.